Requerimientos nutricionales de macroelementos NPK en el cultivo de Tabaco (Nicotiana tabacum) y su efecto sobre la calidad de la Hoja - Chiriguay Cabezas., Isabel Stefanie (2020)
Tobacco is a dicotyledonous plant that came to Europe from America, being its first uses as an ornamental plant, then as a medicinal plant and finally used in the tobacco industries. In Ecuador, tobacco contributes 18% of the total income tax and 46% of the global collections of the consumption tax, as well as generating income for the country from its production, with an average yield of 2.24 metric tons per hectare. The areas of greatest cultivation are Simón Bolívar, Naranjal, Milagro, El Empalme, Mocache and Quevedo, the latter being areas that have adequate edaphoclimatic conditions for the production of tobacco cultivation. Knowledge of the fertility of the soil and the fertilization of the fields is of great importance in tobacco production, since the purpose of this is to produce a leaf with a well-defined chemical composition and certain physical conditions, capable of meeting the important requirement known as quality. The nutritional management of the crop is an essential tool of any modern production approach. The essential nutrients that most limit tobacco production systems are macroelements such as nitrogen, phosphorus and potassium. Tobacco cultivation in Ecuador is considered a crop that provides employment to many families due to the different activities that are developed to obtain the final product, it is also a crop that can contribute to the economic and social sector. Therefore, it is necessary to establish fertilization programs based on a soil analysis and nutritional requirement of the crop. Among the main nutrients that tobacco needs in the highest content are nitrogen, phosphorus and potassium; known as essential macroelements. Among the situations that arise in tobacco cultivation is mainly the execution of an edaphic fertilization program, application of the necessary elements that favor the phenology of tobacco cultivation, which acts at the same time as preventive measures against nutritional deficit that hinders the production of leaves, commercialization and development of plants.